An exploration of family members perceptions of palliative care given to dementia patients and their families in old age homes in Cape Town - Miller, Deborah Lee (Department of Public Health and Family Medicine, 2015)
The disease trajectory that characterises dementia is one of progressive neuro-psychiatric, physical and cognitive decline. It is family members who often bear the brunt of the suffering that these sequential 'deaths' and losses bring. As they retain strong bonds, placement of loved ones in an institution is often seen as the ultimate act of betrayal resulting in ongoing guilt. How families perceive care given in these homes, the relationships they form with staff and the new roles they take depends on multiple variables. Although this has been the subject of some studies in the USA, UK and Europe, there is at yet no research on this phenomenon in South Africa and Africa as a whole. This study utilised Interpretative Phenomenological Analysis (IPA) to explore the experience of 10 family members of 8 patients with moderately severe to severe dementia in 5 different old age homes in Cape Town. IPA seeks to give a credible account of the interpretation of the person's experience, by using a deeper analysis whilst remaining firmly anchored in the participants account. The analysis and discussion of this study were conducted by the primary researcher and corroborated by an independent Social Worker experienced in psychoanalysis. The discussion was integrated with the literature review to enhance validity and place this research within the context of broader research on the subject. Analysis of emergent themes revealed that family members enter old age homes with a prior agenda shaped by their experiences prior to admission. Home placement is an extremely traumatic event and carries with it an ongoing heavy burden of guilt. The unwillingness or inability of medical professionals to provide information significantly increases that burden. Perceptions of how staff and administrators may think or function are often negative and distrustful and may well be misconceived. None the less they are believed to be true and heavily influence the integration of families into the home in either a positive or negative way. Old racial divides entrenched during Apartheid still hold sway and influence reactions towards and from nursing staff. Ultimately families still seek to play an active role in their loved ones lives and to seek purpose in their relationships.